Maternidade, consumo e sustentabilidade sob a ótica ecofeminista - Riemenschneider, Patricia Strauss (My University, 2016)
Current western societies try to influence women, particularly mothers; regarding their behavior and conduct in relation to the way they raise their children. Through practices ingrained and established, it is spread that everything derived from technology and development is better and consequently brings more benefits to the child than those which are natural and instinctive. The practice of arranged caesareans, the use of artificial milk, the non-use of a shared bed or room, as well as the use of industrialized and processed foods in the diet of the children to be, “modern” and “contemporary”. On the contrary, a natural birth, breast feeding and the practice of a shared bed, as well as foods based on natural products are “outdated”, “inconvenient” and “old-fashioned”. However, current practices derived from “development” not only fail to bring health benefits to the children, but are also not “sustainable” processes. They have high production costs, generate waste and harmful disposal to the environment and to the Earth’s natural resources. Ecofeminism understands the mitigation of female leadership and the exploration of nature are consequences of the same phenomenon; male domination over both that exists in systems of oppression as well as patriarchate. Through various assumptions which put women and nature in a regime of submission, treat women as incompetent and incapable of raising their children and nature as a mere source of resources, there to be degraded and exploited. The philosophy of ecofeminism theoretically underlies this, as does this study, and addresses within their different branches, the illusion that everything “technological” and “developed” is better than what is “natural” and “instinctive”, when in reality, what happens is the exact opposite; the return to our origins and primitive practices related to maternity, as well as being sustainable are infinitely better for the health of our future generations.
As sociedades ocidentais atuais tentam influenciar as mulheres e, em especial, as mães, sobre comportamentos e condutas na criação de seus filhos. Através de práticas enraizadas e estabelecidas, propagam que tudo que for derivado da tecnologia e do desenvolvimento é melhor e traria, como consequência, mais benefícios para a prole do que que o for instintivo e natural. A prática de cesáreas agendadas, o uso de leite artificial, o desaconselhamento ao uso da cama ou cômodo compartilhado, bem como a utilização de alimentos industrializados e processados na nutrição dos filhos seriam, desta forma, práticas “modernas” e “contemporâneas”. Já, em contrapartida, o parto natural, o aleitamento materno, a prática da cama compartilhada, bem como a alimentação baseada em produtos naturais seriam condutas “anacrônicas”, “inconvenientes” e “ultrapassadas”. No entanto, as práticas atuais e derivadas do “desenvolvimento não só não trazem benefícios para a saúde dos filhos, como também não são praticas ditas “sustentáveis”. Possuem altos custos de produção, além de gerar resíduos e descarte degradando, assim, o meio ambiente e diminuindo os recursos naturais do Planeta. O Ecofeminimo entende que a mitigação do protagonismo feminino e a exploração da Natureza são consequências de um mesmo fenômeno: a dominação masculina sobre ambas que existe em sistemas de opressão, como o patriarcado. Através de várias premissas, coloca mulheres e Natureza em um regime de submissão: trata a mulher como incompetente e incapaz para o ato de parir e de cuidar da prole e a Natureza como uma mera fonte de recursos, apta a ser degradada e explorada. A Filosofia Ecofeminista embasa teoricamente, assim, o presente estudo, já que trata, dentro de suas diferentes correntes, sobre a falácia de que tudo que for “tecnológico” e “desenvolvido” seria melhor que o “natural” e “instintivo”, quando na verdade, o que ocorre, é exatamente o contrário: o retorno às origens e às práticas primitivas relativas à maternidade, além de ser sustentável, também é, infinitamente melhor para a saúde das futuras gerações.
Keywords: Ecofeminismo; Sustentabilidade; Sociedade de consumo; Maternidade - Aspectos sociais; Ecofeminism; Sustainability; Consumer society